Learning Styles and Psychological Preferences among Christian Disciples. (May 2015) - Francis, Leslie J.; Robbins, Mandy
<x content-type="archive" xml:space="preserve">Abstract</x> This paper offers an audit of the BA in Theology for Discipleship and Ministry by examining the learning styles and psychological preferences of 108 course participants (66% response rate) who completed the Francis Psychological Type Scales and the Francis Inventory of Learning Styles. The data demonstrated that the adult learners displayed strong preferences for introversion over extraversion, for sensing over intuition, and for judging over perceiving, as well as a balance of preferences for thinking and for feeling. In spite of the clear personal preferences of the course participants, appreciation was shown for a mixed learning experience, embracing extravert learning preferences as well as introvert learning preferences, intuitive learning preferences as well as sensing learning preferences, feeling learning preferences as well as thinking learning preferences, and judging learning preferences. Only perceiving learning preferences were not so widely welcomed by the course participants. The implications of these findings were assessed both for educational practice and for further research.